Psychological experiences and quality of life in patients awaiting coronary artery bypass graft - Al-Hassan, Mousa; Ahmed, Samira; Akhu-Zahea, Laila; Hayudini, Jahara (International Journal of Advanced Nursing Studies, 2014)
Background: Coronary artery bypass graft surgery improves quality of life and survival rates. However, prolonged waits for this surgery are inevitable in countries having nationalized healthcare systems. Although no significant decline in the waiting times for this surgery has been demonstrated, recent research in psychological experiences of the patients is lacking Objectives: 1)     To describe psychological experiences, anxiety and uncertainty, and quality of life in Omani patients awaiting coronary artery bypass graft. 2)     To examine the significance of sociodemographics, health characteristics and the waiting time in predicting anxiety and uncertainty. 3)     To examine the independent effect of anxiety and uncertainty in predicting quality of life of the patients. Methods: This study used a cross-sectional design. To obtain the required information, two nurses interviewed a convenience sample of hospitalized patients for coronary artery bypass graft (N = 84) between May 2011 and June 2012. Three regression analyses were used to identify significant predictors of anxiety, uncertainty and quality of life. Results: Literate patients and those with infrequent hospital admissions were more likely to experience high levels of anxiety, whereas, patients without myocardial infarction but having hypertension, and those who waited for the surgery 60 days or less were more likely to report greater uncertainty.  Exercising regularly, low family monthly income and short duration since diagnosis with coronary artery disease significantly predicted better quality of life Conclusion: Physiological disruptions and concomitant chronic illnesses have significant effects on the psychological experiences and quality of life of the patients.   Keywords: Anxiety, Coronary Artery Bypass Graft, Quality Of Life, Uncertainty, Waiting Time.